Sonatas for pianoforte and violoncello - Beethoven, Ludwig van 1770-1827; Del Mar, Jonathan (Kassel Bärenreiter, 2016)
Awarded with the German Music Edition Prize "Best Edition" 2005Scholarship has advanced, new sources have come to light and the renowned Beethoven expert Jonathan Del Mar has turned his attention to the centrally important works in the cello oeuvre , the five Beethoven Sonatas for Violoncello and Piano.Jonathan Del Mar's scholarly-critical edition not only contains the definitive music text, but also the first critical commentary to these works.